Demographic and Clinical Characteristics of Patients With Charcot Neuro-Osteoarthropathy in People With Diabetes Mellitus in Six Countries: A Multicenter Observational Study From 1996 to 2022 - E. B. Jude; C. Siafarikas; A. Rastogi; R. Bem; T. Tankova; M.-F. Kong; J. LaFontaine; J. Pappachan; N. Tentolouris (Journal of Diabetes Research)
Conclusions: CNO is predominant in males, occurs in long-standing DM, and is often accompanied by microvascular complications. People with T1DM, compared to those with T2DM, are affected at a younger age, have longer diabetes duration, and have more often microvascular complications.